Pengaruh Model Contextual Teaching and Learning terhadap Hasil Belajar Kognitif Siswa pada Tema 5 Subtema 3 Kelas III SDN Batang-Batang Daya II - Isro Riskiyanto; Agung Setyawan (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research was conducted with the aim of knowing the Effect of Contextual Teaching And Learning Model on Students' Cognitive Learning Outcomes on Theme 5 Subtheme 3 Class III SDN Batang-Batang Daya II. This research is a quantitative study that uses the experimental method, with a Pre-Experimental design using the One-Group Pre-Test Post-Test Design. Data collection was carried out using the sampling method from the population. The number of students sampled was 21 students. Data was collected through giving Pre-Test and Post-Test questions. The results showed that the application of the Contextual Teaching and learning (CTL) learning model had a significant impact on student learning outcomes. The significance level of the results of the Paired sample T-Test test shows a value of 0.000, this indicates that there is a significant difference found in the effect. Based on the testing criteria if the Sig. (2-tailed) <0.05 (0.000<0.05) then Ho is rejected and Ha is accepted. This means that there is a significant influence in the application of the Contextual Teaching And Learning Model on Students' Cognitive Learning Outcomes on Theme 5 Subtheme 3 Class III SDN Batang-Batang Daya II.